Isolasi Senyawa Aktif Ekstrak Etanol Biji Alpukat (Persea americana) dan Uji Toksisitas Terhadap Artemia Salina Leach - Abubakar, Andi Nur Fitriani; Aisyah, Aisyah; Baharuddin, Maswati (Al-Kimia, 2014)
Avocado seed (Persea americana) is recognized as one of medicinal plants. It contains several secondary metabolites, which have toxic activity. However, efforts to identify active compounds from avocado seeds (Persea americana) are still relatively rare. Therefore, isolation and toxicity assay have been conducted foward the active compound of avocado seed. Maceration one kilogram of seed dried powder by ethanol obtained 49,7464 gram extract. Separation of etanol extract by column chromatography generated 0,0698 grams of pure white needle crytal, which is positively triterpenoid based on Lieberman-Buchard test. In addition, infrared spectrum showed the existence of OH, C=C, C-C, C=O, -C-H, -CH3,-CH2 and C-O stretch, which support the presumed compound. The result of toxicity test on Artemia salina Leach showed that the extract, fraction and pure isolates of the etanol extract are toxic with LC50 values 13,274 g/mL; 9,528 g/mL and 8,128 g/mL, respectively.